SYNTHESIS OF CALCIUM-ALUMINOSILICATE USING ALGINAT-CHITOSAN TEMPLATE FOR WATER FILTER APPLICATIONS VIA SOL-GEL PROCESS - ISMA ANINDITA (NIM : 13707068); Pembimbing : Dr. Ir. Bambang Sunendar P., M. Eng., TIARA
In order to minimalize health problems caused by lack of clean water for consumption after natural disaster, there’s a need for the simple and portable water filtering system, for example a nanoporous ceramic membrane. In this study, a calcium-aluminosilicate zeolite was synthesized through the sol-gel method followed by vacuum process. Sodium silicate was used as silica precursor, Aluminium nitrate as alumina precursor, and Calcium phosphate as calcium precursor. As the template, alginate and chitosan was mixed with CaCl2 in volume ratio 2:2:1. There’s a variation of sodium silicate concentration, 0.5M, 1M, and 1.5M. Sample was examined through the characterization such as XRD, FTIR, SEM and BET. XRD datas showan amorphous phase formation of samples. FTIR spectra shows peaks at ~550 -500cm-1 for for for for (Al-O-C), (Si-O-Al), (Si-O), and (Si-O-Si). SEM datas for sample 1 (sodium silicate 1.5M) shows a uniformly growth membrane. BET datas show it’s specific surface area 30.1266 m2/g.